Me and My Brand – A Study on Employee Perspective - Radha Kiranmayi, G.; Jyothi, P. (Prabandhan: Indian Journal of Management, 2017)
An individual is known by his/her personality. Personality, an area studied for almost a century by theorists, psychologists, and researchers, is one of the important determinants of individual behaviour. But the question of 'how it affects the work action' is yet to be properly answered. The studies on understanding the role of personality in different aspects of work behavior are still an area of interest for many inquisitive researchers. This study on similar grounds tried to examine the role of personality factors on employee brand identification in internal brand management. A survey was conducted administering a structured questionnaire on a sample of 232 employees of select IT & ITES companies in Hyderabad. The results indicated that an individual's personality factors affect employee brand identification, and therefore, highlight the importance of having an appropriate person with appropriate personality at work for achieving great results. Therefore, it was implied that, it is important for both branding and HR personnel of the organizations to work in harmony with each other to identify and create a perfect blend of human resources by considering and evaluating the prospect's personality fit along with the technical skills and competencies. Such human resources would then reflect the organization's brand identity as their own identity, thus achieving maximum employee and customer experience.